Systemic Therapy for Advanced Soft Tissue Sarcomas - Riedel, Richard F (Wiley Subscription Services, Inc., A Wiley Company, 2012)
Soft tissue sarcomas (STS) are a rare, heterogeneous group of solid tumors in need of improved therapeutic options. First-line chemotherapy is considered the current standard of care for patients with advanced, symptomatic STS, but the median survival is only 8 to 12 months. Efforts to increase response rates by using combination or dose-dense regimens have largely failed to improve patient outcomes. However, increasing evidence supports the use of specific treatments for certain histological subtypes of STS, and novel therapies, including tyrosine kinase and mammalian target of rapamycin inhibitors, are currently under active investigation. In addition, novel treatment approaches (such as maintenance therapy) designed to prolong the duration of response to chemotherapy and delay disease progression are being explored. This article provides an overview of current systemic therapies for patients with advanced STS and discusses ongoing efforts designed to improve patient outcomes through the use of novel therapeutic agents and treatment strategies. Cancer 2011;. © 2011 American Cancer Society. Soft tissue sarcomas (STS) are a rare, heterogeneous group of solid tumors in need of improved therapeutic options. This article provides an overview of current systemic therapies for patients with advanced STS and discusses ongoing efforts designed to improve patient outcomes through the use of novel therapeutic agents and treatment strategies.